Polymer, composition, negative electrode and battery using same

By employing polymers with lithium sulfonate groups that react with silicon-containing materials, the issues of low efficiency and volume swelling in lithium battery negative electrodes are addressed, resulting in improved stability and extended cycle life.

JP7669461B2Active Publication Date: 2025-04-28IND TECH RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023214852
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-12-20
Publication Date
2025-04-28
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

The use of silicon-containing materials as active materials in lithium battery negative electrodes leads to low efficiency and significant volume swelling, which severely impacts the cycle life of lithium batteries.

Method used

The development of polymers with lithium sulfonate groups that can react with silicon-containing compounds, forming structures with lithium replenishment functionality and high mechanical strength, thereby stabilizing the anode active layer and preventing volume swelling.

Benefits of technology

The proposed solution enhances the stability of the negative electrode, improves battery efficiency, and extends the cycle life by mitigating volume swelling and maintaining mechanical integrity during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669461000011
    Figure 0007669461000011
  • Figure 0007669461000012
    Figure 0007669461000012
  • Figure 0007669461000001
    Figure 0007669461000001
Patent Text Reader

Abstract

To provide a composition of a negative electrode active layer that can improve battery efficiency and cycle life.SOLUTION: The present invention provides a polymer with a repeating unit of formula (I), a composition including the polymer, a negative electrode prepared from the composition, and a battery including the same, where R1 is hydrogen or an acetyl group, R2's independently represent hydrogen, -SO3H, or -SO3Li, and at least one of R2's is -SO3Li.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polymers, compositions, anodes and batteries using the same. [Background technology]

[0002] Lithium-ion secondary batteries are the mainstream commercial product, and they are currently being developed to be lighter, smaller in volume, and safer, as well as to have higher energy capacity and longer cycle life. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] U.S. Patent No. 5,229,504A Summary of the Invention [Problem to be solved by the invention]

[0004] Carbon materials are widely used as the active material of the negative electrode of lithium batteries. In order to further increase the battery capacity, lithium batteries have been developed toward using silicon-containing materials as the active material in the negative electrode. However, when silicon-containing materials are used as the active material in the negative electrode, the coulombic efficiency of the battery is reduced. In addition, the phenomenon of volume swelling of silicon-containing materials has a great influence on the cycle life of lithium batteries, which is a major obstacle to the application of silicon-containing materials to lithium battery negative electrodes. [Means for solving the problem]

[0005] The present disclosure provides polymers, compositions, anodes, and batteries using the same. The polymers have repeat units of formula (I).

[0006] [ka]

[0007] In the formula, R 1 is hydrogen or an acetyl group, and R 2 are each independently hydrogen, -SO3H, or -SO3Li, and R 2 At least one of the is -SO3Li.

[0008] According to an embodiment of the present disclosure, the present disclosure also provides a composition. The composition includes component (A) and component (B). Component (A) includes polymer (A-1) (having a repeating unit of formula (I)) of the present disclosure. Component (B) is a binder. Here, the weight ratio of component (A) to component (B) may be 1:1 to 1:9.

[0009] According to an embodiment of the present disclosure, the present disclosure also provides a negative electrode, the negative electrode including a negative electrode active layer, the negative electrode active layer being made from a composition of the present disclosure.

[0010] According to an embodiment of the present disclosure, the present disclosure also provides a battery. The battery includes the negative electrode of the present disclosure, a separator, and a positive electrode, the negative electrode being separated from the positive electrode by the separator. Effect of the Invention

[0011] The present disclosure provides a polymer, a composition (e.g., a composition of a negative electrode active layer), a negative electrode (e.g., a negative electrode of a lithium battery), and a battery (e.g., a lithium battery) using the same. According to an embodiment of the present disclosure, the polymer of the present disclosure has a lithium sulfonate group, and can react with a compound having a hydroxyl group or a silicon-containing compound. By adding the polymer of the present disclosure, the composition of the present disclosure can form a structure having lithium replenishment functionality and high mechanical strength, which increases the stability of the active layer of the negative electrode and suppresses the occurrence of volume swelling of the negative electrode during charging and discharging. As a result, the efficiency and cycle life of the battery can be improved.

[0012] The present invention can be more fully understood from the following detailed description and examples, taken in conjunction with the accompanying drawings. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a cross-sectional view of a negative electrode of a battery according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view of a battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The polymer, composition, anode and battery using the same of the present disclosure will be described in detail in the following description. In the following detailed description, for the purpose of explanation, numerous specific details and embodiments are set forth to fully understand the present disclosure. The specific elements and configurations described in the following detailed description are set forth to clearly explain the present disclosure. However, it will be apparent that the exemplary embodiments shown herein are merely used for the purpose of explanation, and the inventive concept can be embodied in various forms without being limited to these exemplary embodiments. In addition, in order to clearly explain the present disclosure, similar and / or corresponding numerals may be used in the drawings of different embodiments to indicate similar and / or corresponding elements. However, the use of similar and / or corresponding numerals in the drawings of different embodiments does not imply any correlation between different embodiments. As used herein, the term "about" in quantitative terms refers to plus or minus an amount that is common and reasonable to those skilled in the art.

[0015] It should be noted that elements or devices in the drawings of this disclosure may be presented in any form or configuration known to one of ordinary skill in the art. Additionally, the phrases "a layer over another layer," "a layer disposed on top of another layer," "a layer disposed on another layer," and "a layer disposed above another layer" may refer to a layer that is in direct contact with another layer, and they may also refer to a layer that is not in direct contact with another layer, but has one or more intermediate layers between them.

[0016] The depicted figures are only schematic and non-limiting. For illustrative purposes, the size, shape or thickness of some components in the figures may be exaggerated and not drawn to scale. The dimensions and relative dimensions do not correspond to an actual location for practicing the present disclosure. Although the present disclosure will be described with respect to certain embodiments and with reference to certain figures, the present disclosure is not limited thereto.

[0017] According to an embodiment of the present disclosure, the polymer of the present disclosure may have a recurring unit of formula (I).

[0018] [ka]

[0019] In the formula, R 1 may be hydrogen or an acetyl group, R 2 may each independently be hydrogen, -SO3H, or -SO3Li; R 2 At least one of the repeat units is -SO3Li. According to an embodiment of the present disclosure, the polymer of the present disclosure may have at least one repeat unit of formula (I).

[0020] According to an embodiment of the present disclosure, the recurring unit of formula (I) may be any of the following:

[0021] [ka]

[0022] In the formula, R 1 can be hydrogen or an acetyl group.

[0023] According to an embodiment of the present disclosure, the recurring unit of formula (I) may be any of the following:

[0024] [ka]

[0025] In the formula, R 2 may each independently be hydrogen, -SO3H, or -SO3Li; R 2 At least one of the is -SO3Li.

[0026] According to an embodiment of the present disclosure, the recurring unit of formula (I) may be any of the following:

[0027] [ka]

[0028] According to an embodiment of the present disclosure, the weight average molecular weight (Mw) of the polymer of the present disclosure is about 100,000 g / mol to 900,000 g / mol (e.g., 150,000 g / mol, 200,000 g / mol, 300,000 g / mol, 500,000 g / mol, 700,000 g / mol, or 800,000 g / mol). The weight average molecular weight (Mw) of the oligomer or polymer of the present disclosure can be measured by gel permeation chromatography (GPC) (based on a polystyrene calibration curve).

[0029] According to an embodiment of the present disclosure, a method for making a polymer having a repeating unit of formula (I) of the present disclosure may include the following steps: first, prepare chitosan; then react the chitosan with chlorosulfonic acid to proceed sulfonation to obtain chitosan having sulfo groups; then react the chitosan having sulfo groups with lithium hydroxide to obtain a polymer having a repeating unit of formula (I).

[0030] According to an embodiment of the present disclosure, the present disclosure also provides a composition (e.g., a binder composition). According to an embodiment of the present disclosure, the composition may include component (A) and component (B). Component (A) may include polymer (A-1) (having a repeating unit of formula (I)) of the present disclosure. Component (B) may be a binder. According to an embodiment of the present disclosure, the weight ratio of component (A) to component (B) may be about 1:1 to 1:9, for example, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or 1:8. When the weight ratio of component (A) to component (B) is within the above-mentioned range, the composition of the present disclosure exhibits excellent adhesive ability.

[0031] According to another embodiment of the present disclosure, component (A) may consist of polymer (A-1) of the present disclosure (having repeat units of formula (I)).

[0032] According to an embodiment of the present disclosure, component (A) may further include carboxymethylcellulose (CMC) (A-2) to enhance the adhesive ability of the composition. According to another embodiment of the present disclosure, component (A) may be a combination of the polymer (A-1) of the present disclosure and carboxymethylcellulose (CMC) (A-2). That is, component (A) may consist of the polymer (A-1) of the present disclosure and carboxymethylcellulose (CMC) (A-2).

[0033] According to an embodiment of the present disclosure, the weight ratio of polymer (A-1) to carboxymethylcellulose (CMC) (A-2) may be about 99:1 to 1:19, such as 95:1, 90:1, 85:1, 80:1, 75:1, 70:1, 65:1, 60:1, 55:1, 50:1, 45:1, 40:1, 35:1, 30:1, 25:1, 20:1, 15:1, 10:1, 5:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or 1:15. According to an embodiment of the present disclosure, the polymer of the present disclosure may react with methylcellulose to form a network structure.

[0034] According to an embodiment of the present disclosure, the binder (i.e., component (B)) may be polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), poly(styrene-co-butadiene), fluororubber, polyurethane, polyvinylpyrrolidone, polyvinyl carbonate, polyvinyl chloride, polyacrylonitrile (PAN), polybutadiene, polyacrylic acid (PAA), perfluoroalkoxyalkane (PFA), fluorinated ethylene propylene (FEP), polyvinylidene fluoride-co-hexafluoropropene (PVDF-HFP), styrene-butadiene rubber (SBR), acrylic resin, polyethylene glycol (PEG), poly(ethylene oxide) (PEO), or a combination thereof. According to embodiments of the present disclosure, the weight average molecular weight (Mw) of the binder of the present disclosure may be from about 100,000 g / mol to 9,000,000 g / mol (e.g., 200,000 g / mol, 300,000 g / mol, 500,000 g / mol, 700,000 g / mol, 1,000,000 g / mol, 1,300,000 g / mol, 1,500,000 g / mol, 2,000,000 g / mol, 32,000,000 g / mol, 4,000,000 g / mol, 5,000,000 g / mol, 6,000,000 g / mol, 7,000,000 g / mol, or 8,000,000 g / mol). The weight average molecular weight (Mw) of the binders of the present disclosure can be measured by gel permeation chromatography (GPC) (based on a polystyrene calibration curve).

[0035] According to an embodiment of the present disclosure, the composition may further include component (C), and component (C) may be a negative electrode active material. According to an embodiment of the present disclosure, the negative electrode active material may be a carbon material, lithium, a transition metal oxide, a lithium-containing compound, a silicon-containing material, or a combination thereof. According to an embodiment of the present disclosure, the carbon material may include metastable phase spherical carbon (MCMB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), coke, carbon black, graphite, graphene, acetylene black, carbon fiber, or a combination thereof. According to an embodiment of the present disclosure, the lithium-containing compound may include LiAl, LiMg, LiZn, Li3Bi, Li3Cd, Li3Sb, Li4Si, Li 4.4 Pb, Li 4.4 Sn, LiC6, Li3FeN2, Li 2.6 Co 0.4 N, or Li 2.6 Cu 0.4 According to an embodiment of the present disclosure, the silicon-containing material may include carbon-modified silicon oxide, silicon carbide, or pure silicon materials. According to an embodiment of the present disclosure, the transition metal oxide may include Li4Ti5O 12 or TiNb2O7. According to an embodiment of the present disclosure, the ratio of the total weight of components (A) and (B) to the weight of component (C) may be about 1:5 to 1:15, for example, 1:6, 1:7, 1:8, 1:9, 1:10, or 1:13.

[0036] According to an embodiment of the present disclosure, the composition may further include component (D), and component (D) is a conductive material. According to an embodiment of the present disclosure, the conductive material may be conductive carbon black, conductive graphite, fluorocarbon, reduced graphene, nitrogen-doped graphite, nitrogen-doped graphene, carbon fiber, carbon nanotubes, or a combination thereof. According to an embodiment of the present disclosure, the ratio of the total weight of components (A) and (B) to the weight of component (D) may be 1:1 to 1:9, for example, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or 1:8.

[0037] According to an embodiment of the present disclosure, the composition of the present disclosure may be a negative electrode active layer composition used to prepare a negative electrode active layer, which becomes the negative electrode of a battery. The composition may include component (A), component (B), component (C), and component (D). According to an embodiment of the present disclosure, the composition may include about 0.1 wt % to 6 wt % (e.g., 0.2 wt %, 0.3 wt %, 0.5 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, or 5.5 wt %) of component (A) and 1 wt % to 10 wt % (e.g., 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %) of component (B) based on the total weight of component (A), component (B), component (C), and component (D). , 8 wt%, or 9 wt%) of component (C), 65 wt% to 90 wt% (e.g., 70 wt%, 75 wt%, 80 wt%, 82 wt%, or 84 wt%) of component (C), and 1 wt% to 20 wt% (e.g., 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 12 wt%, 15 wt%, 17 wt%, 18 wt%, or 19 wt%) of component (D).

[0038] According to another embodiment of the present disclosure, the composition may consist of component (A), component (B), component (C) and component (D).

[0039] According to the embodiment of the present disclosure, a highly adhesive protective layer (formed from component (A) and component (B)) is formed on the surface of component (C), which can increase the surface flatness of the negative electrode during charging and discharging, and can suppress or reduce the formation of metal dendrites. As a result, the performance and life of the battery (e.g., lithium battery) are improved. In addition, when component (C) is a silicon-containing material, component (A) reacts with the silicon-containing material to achieve compact encapsulation of the silicon-containing material, which can withstand the stress generated during charging and discharging, thereby avoiding the phenomenon of volume swelling of the silicon-containing material during charging and discharging. This contributes to achieving the purpose of improving the cycle life of silicon-based negative electrodes.

[0040] According to an embodiment of the present disclosure, when component (A) is composed of a polymer and methylcellulose, a network structure can be formed to cover the surface of component (C).

[0041] According to an embodiment of the present disclosure, the composition further comprises component (E), and components (A), (B), (C) and (D) are uniformly dispersed in component (E) to form a slurry (used in the coating process), whereby components (A), (B), (C) and (D) are thoroughly mixed. According to an embodiment of the present disclosure, component (E) may be water, ethylene glycol dimethyl ether (DME), 1-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), pyrrolidone, N-dodecylpyrrolidone, γ-butyrolactone or a combination thereof. According to an embodiment of the present disclosure, when the composition comprises component (E), the solid content of the composition may be about 5 wt% to 30 wt%, for example, 6 wt%, 10 wt%, 15 wt%, 20 wt%, or 25 wt%. Here, the solid content means the weight percentage of the components of the composition, excluding component (E), relative to the total weight of the composition.

[0042] According to another embodiment of the present disclosure, the composition may consist of component (A), component (B), component (C), component (D), and component (E).

[0043] According to an embodiment of the present disclosure, due to the specific components and contents of the composition of the present disclosure, the negative electrode made from the composition has a function of lithium replenishment and a structure with high mechanical strength, thereby increasing the stability of the negative electrode, suppressing the occurrence of volume expansion of the negative electrode, and improving the efficiency and cycle life of the battery.

[0044] According to an embodiment of the present disclosure, the present disclosure provides an anode that is a battery anode (e.g., a lithium battery anode). According to an embodiment of the present disclosure, as shown in FIG. 1, the anode 10 of the present disclosure may include an anode active layer 12. According to an embodiment of the present disclosure, the anode active layer 12 may be made from the composition of the present disclosure after mixing or reaction. According to an embodiment of the present disclosure, the thickness of the anode active layer 12 of the present disclosure is not limited and may be arbitrarily changed by a person having ordinary skill in the art. For example, the thickness of the anode active layer 12 may be about 1 μm to 1,000 μm (e.g., about 5 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, or 900 μm).

[0045] In addition, as shown in FIG. 1, the negative electrode 10 may further include a negative electrode current collecting layer 14, and the negative electrode active layer 12 is disposed on the negative electrode current collecting layer 14. According to an embodiment of the present disclosure, the thickness of the negative electrode current collecting layer 14 is not limited and can be arbitrarily changed by a person having ordinary skill in the art. For example, the thickness of the negative electrode current collecting layer 14 may be about 100 μm to 5,000 μm (e.g., about 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1,000 μm, 2,000 μm, 3,000 μm, or 4,000 μm). According to an embodiment of the present disclosure, the negative electrode current collecting layer 14 may be a conductive carbon substrate, a metal foil, or a metal material having a porous structure, such as carbon cloth, carbon felt, carbon paper, copper foil, nickel foil, aluminum foil, nickel mesh, copper mesh, molybdenum mesh, nickel foam, copper foam, or molybdenum foam. According to an embodiment of the present disclosure, the porosity of the metal material having a porous structure may be about 10% to 99.9% (e.g., 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%).

[0046] According to another embodiment of the present disclosure, the negative electrode 10 may be comprised of a negative electrode active layer 12. According to another embodiment of the present disclosure, the negative electrode 10 may be comprised of a negative electrode active layer 12 and a negative electrode current collecting layer 14.

[0047] According to an embodiment of the present disclosure, a method for preparing the negative electrode 10 shown in FIG. 1 may include the following steps: First, prepare a negative electrode current collecting layer (e.g., copper foil) 14. Then, component (A), component (B), component (C) and component (D) are uniformly dispersed in component (E) (i.e., solvent) for a certain time (about 30 minutes to 6 hours, e.g., 1 hour, 2 hours, 3 hours, or 5 hours) to obtain a composition of the present disclosure (become a negative electrode active layer slurry). Then, the composition is applied to the surface of the negative electrode current collecting layer 14 by a coating process to form a coating. Then, the coating is subjected to a rolling process (compression ratio of about 15% to 70%, e.g., 20%, 30%, 40%, 50%, or 60%) and a drying process (temperature 90 o C to 180o C (e.g. 100 o C, 120 o C, or 150 o C) for 30 minutes to 18 hours (e.g., 1 hour, 3 hours, 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, or 15 hours) to obtain the negative electrode active layer 12. The coating process may be screen printing, spin coating, bar coating, blade coating, roller coating, solvent casting, or dip coating.

[0048] According to an embodiment of the present disclosure, the present disclosure also provides a battery 100, for example a lithium battery, a lithium ion battery, or a lithium metal battery, as shown in FIG. 2. The battery 100 includes an anode 10, a separator 20, and a cathode 30, as shown in FIG. 1, in which the anode 10 is separated from the cathode 30 by the separator 20. According to an embodiment of the present disclosure, the cathode 30 may be in direct contact with the separator 20, and / or the anode 10 may be in direct contact with the separator 20. According to an embodiment of the present disclosure, the cathode 30 may be spaced apart from the separator 20 by a specific distance, and / or the anode 10 may be spaced apart from the separator 20 by a specific distance. According to an embodiment of the present disclosure, the battery 100 may further include a liquid electrolyte 40, which is disposed between the anode 10 and the cathode 30. That is, the laminated structure of the anode 10, the separator 20, and the cathode 30 is immersed in the liquid electrolyte 40. That is, the battery 100 is filled with a liquid electrolyte. According to some embodiments of the present disclosure, the negative electrode active layer 12 of the present disclosure may be disposed between the separator 20 and the negative electrode current collecting layer 14. According to embodiments of the present disclosure, the battery 100 of the present disclosure may comprise the negative electrode 10, the separator 20, the positive electrode 30, and the liquid electrolyte 40.

[0049] According to an embodiment of the present disclosure, the separator 20 may include an insulating material, such as polyethylene (PE), polypropylene (PP), polytetrafluoroethylene (PTFE), polyamide, polyvinyl chloride (PVC), poly(vinylidene fluoride), polyaniline, polyimide, polyethylene terephthalate, polystyrene (PS), a ceramic material, or a combination thereof. For example, the separator 20 may be a multi-layer composite structure. According to an embodiment of the present disclosure, the separator may have a porous structure. That is, the pores of the separator are uniformly distributed throughout the separator.

[0050] According to an embodiment of the present disclosure, the liquid electrolyte 40 may include a solvent and a lithium salt (or a lithium-containing compound). According to an embodiment of the present disclosure, the negative electrode active material (i.e., component (C)) is encapsulated in a protective layer (made of components (A) and (B)). Thus, the protective layer prevents the negative electrode active material from directly contacting the liquid electrolyte, thereby reducing decomposition of the liquid electrolyte and improving the cycle performance of the battery.

[0051] According to an embodiment of the present disclosure, the liquid electrolyte 40 of the present disclosure is not limited and may be a conventional liquid electrolyte used in lithium batteries. According to an embodiment of the present disclosure, the concentration of the lithium salt in the solvent may be about 0.8M to 1.6M, such as about 0.9M, 1.0M, 1.1M, 1.2M, 1.3M, 1.4M, or 1.5M. According to an embodiment of the present disclosure, the solvent may be an organic solvent, such as an ester-based solvent, a ketone-based solvent, a carbonate-based solvent, an ether-based solvent, an alkane-based solvent, an amide-based solvent, or a combination thereof. According to an embodiment of the present disclosure, the solvent may be 1,2-diethoxyethane, 1,2-dimethoxyethane, 1,2-dibutoxyethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, dimethylacetamide (DMAc), 1-methyl-2-pyrrolidone (NMP), methyl acetate, ethyl acetate, methyl butyrate, ethyl butyrate, methyl propionate, ethyl propionate, propyl acetate (PA), gamma-butyrolactone (GBL), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate, butylene carbonate, dipropyl carbonate, fluoroethylene carbonate, 1,3-propane sultone, or a combination thereof.According to an embodiment of the present disclosure, the lithium salt may be any of the following: lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiN(SO2F)2) (LiFSI), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiDFOB), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiSO3CF3), lithium bis(trifluoromethane)sulfonimide (LiN(SO2CF3)2) (LiTFSI), lithium bisperfluoroethanesulfonimide (LiN(SO2CF2CF3)2), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium tetrachloroaluminate (LiAlCl4), lithium tetrachlorogallate (lithium tetrachloride (LiClO4), lithium tetrachlorogallate (LiClO4 ...PF6), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium tetrachloroaluminate (LiAlCl4), lithium tetrachlorogallate (LiClO4), lithium tetrafluoroborate (LiF4), lithium tetrafluoroborate (LiF4), lithium tetrafluoroborate (LiF4), lithium tetrafluoroborate (LiF Lithium tetrachlorogallate (LiGaCl4)), lithium nitrate (LiNO3), tris(trifluoromethanesulfonyl)methyllithium (LiC(SO2CF3)3), lithium thiocyanate hydrate (LiSCN), LiO3SCF2CF3, LiC6F5SO3, LiO2CCF3, lithium fluorosulfonate (LiSO3F), lithium tetrakis(pentafluorophenyl)borate (LiB(C6H5)4), lithium bis(oxalato)borate (LiB(C2O4)2) (LiBOB), or combinations thereof.

[0052] According to an embodiment of the present disclosure, the positive electrode 30 may include a positive electrode active layer 32 and a positive electrode current collecting layer 34, where the positive electrode active layer 32 is disposed on the positive electrode current collecting layer 34 and the positive electrode active layer 32 includes a positive electrode active material.

[0053] According to an embodiment of the present disclosure, the positive electrode active material may be sulfur, an organic sulfide, a sulfur-carbon composite, a lithium-containing metal oxide, a lithium-containing metal sulfide, a lithium-containing metal selenide, a lithium-containing metal telluride, a lithium-containing metal silicide, a lithium-containing metal boride, or a combination thereof, and the metal may be selected from the group consisting of aluminum, vanadium, titanium, chromium, copper, molybdenum, niobium, iron, nickel, cobalt, and manganese. According to an embodiment of the present disclosure, the positive electrode material may be lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium cobalt manganese oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium nickel manganese cobalt oxide, lithium chromium manganese oxide, lithium nickel vanadium oxide, lithium manganese nickel oxide, lithium cobalt vanadium oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or a combination thereof.

[0054] According to an embodiment of the present disclosure, the lithium nickel manganese cobalt oxide of the present disclosure has a structure LiNi x Co y Mn z O2, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1. According to an embodiment of the present disclosure, the lithium nickel cobalt aluminum oxide of the present disclosure may have a structure LiNi 0.80 Co 0.15 Al 0.05 O2. According to an embodiment of the present disclosure, the lithium cobalt oxide of the present disclosure may be LiCoO2.

[0055] According to an embodiment of the present disclosure, the positive electrode active layer 32 may further contain a binder. According to an embodiment of the present disclosure, in the positive electrode active layer 32, the weight ratio of the binder to the positive electrode active material may be from 0.1:99.9 to 10:90 (for example, 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, or 9:91).

[0056] According to an embodiment of the present disclosure, the binder may include polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), styrene-butadiene copolymer, fluororubber, polyurethane, polyvinylpyrrolidone, poly(ethyl acrylate), polyvinyl chloride (PVC), polyacrylonitrile (PAN), polybutadiene, polyacrylic acid (PAA), or a combination thereof. According to an embodiment of the present disclosure, the positive electrode active layer 32 may further include a conductive additive, which may be conductive carbon black, conductive graphite, fluorocarbon, reduced graphene, nitrogen-doped graphite, nitrogen-doped graphene, carbon fiber, carbon nanotube, or a combination thereof. According to an embodiment of the present disclosure, the weight ratio of the conductive additive to the positive electrode active material in the positive electrode active layer 32 may be 0.1:99.9 to 10:90 (e.g., 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, or 9:91). According to another embodiment of the present disclosure, the positive electrode active layer 32 may be composed of a positive electrode active material and a binder. According to another embodiment of the present disclosure, the positive electrode active layer 32 may be composed of a binder, a conductive additive, and a positive electrode active material.

[0057] According to an embodiment of the present disclosure, the positive electrode current collecting layer 34 may be a conductive carbon substrate, a metal foil, or a metal material having a porous structure, such as carbon cloth, carbon felt, carbon paper, copper foil, nickel foil, aluminum foil, nickel mesh, copper mesh, molybdenum mesh, nickel foam, copper foam, or molybdenum foam. According to an embodiment of the present disclosure, the porosity of the metal material having a porous structure may be about 10% to 99.9% (e.g., 60% or 70%).

[0058] According to an embodiment of the present disclosure, the positive electrode active layer 32 of the present disclosure may be disposed between the separator 20 and the positive electrode current collecting layer 34 .

[0059] According to the embodiment of the present disclosure, the thickness of the positive electrode active layer 32 is not limited and can be arbitrarily changed by a person having ordinary skill in the art. For example, the thickness of the positive electrode active layer 32 may be about 1 μm to 1,000 μm (e.g., about 5 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, or 900 μm). According to the embodiment of the present disclosure, the thickness of the positive electrode current collecting layer 34 is not limited and can be arbitrarily changed by a person having ordinary skill in the art. For example, the thickness of the positive electrode current collecting layer 34 can be about 100 μm to 5,000 μm (e.g., about 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1,000 μm, 2,000 μm, 3,000 μm, or 4,000 μm).

[0060] In the following, exemplary embodiments will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily understand. The concept of the present invention is not limited to the exemplary embodiments shown herein, but may be embodied in various forms. For clarity, the description of well-known parts will be omitted, and similar reference numerals will denote similar components throughout. EXAMPLES

[0061] Preparation of polymer Example 1 Chlorosulfonic acid (12 mL) and concentrated sulfuric acid (concentration 17.9 M, 40 mL) were mixed at 0° C. to obtain a mixture. Chitosan (molecular weight about 300,000) (CAS: 9012-76-4, commercially available from sigma-aldrich) was then added to the mixture at 0° C. The equivalent ratio of chitosan to chlorosulfonic acid was about 3:1. The resultant was then reacted at room temperature (25° C.) for 1 hour. The resultant was then added to ethyl ether to precipitate a solid. After filtration, the filter cake was dissolved in deionized water. After filtration, the resultant was titrated with an aqueous lithium hydroxide solution (concentration 1 M) to neutralize. Finally, the solution was dialyzed for 3 days using a dialysis membrane (Cellu-Sep T4) to remove the remaining sulfonic ions. After dialysis, the solution was freeze-dried under low temperature and pressure using a freeze-drying apparatus (FD-8510T) to directly sublimate the water, thereby obtaining polymer (1).

[0062] The results of the nuclear magnetic resonance analysis of the polymer (1) are shown below. 1 H NMR(600MHz,CDCl3):4.92-5.10(H-1),4.50-4.11(H-3,4,5),4.11-3.45(H-6),3.22-2.80(H-2)

[0063] Preparation of negative electrode active layer composition Example 2 80.7 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (commercially available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.6 parts by weight of conductive carbon black (commercially available from Timcal under the trade name Super-P), 2.9 parts by weight of polymer (1), and 3.8 parts by weight of polyacrylic acid (PAA) were mixed and uniformly dissolved in deionized water (for at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (1).

[0064] Example 3 78.9 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (commercially available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.3 parts by weight of conductive carbon black (commercially available from Timcal under the trade number Super-P), 0.5 parts by weight of polymer (1), 4.5 parts by weight of carboxymethyl cellulose (CMC) (commercially available from Daicel Chemical industries under the trade number CMC-2200), and 3.8 parts by weight of styrene butadiene rubber (SBR) (commercially available from Cino Group or S-insight technology under the trade number Nippon A&L 307R) were mixed and uniformly dissolved in deionized water (at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (2).

[0065] Example 4 78.7 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (commercially available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.3 parts by weight of conductive carbon black (commercially available from Timcal under the trade number Super-P), 0.7 parts by weight of polymer (1), 4.5 parts by weight of carboxymethyl cellulose (CMC) (commercially available from Daicel Chemical industries under the trade number CMC-2200), and 3.8 parts by weight of styrene butadiene rubber (SBR) (commercially available from Cino Group or S-insight technology under the trade number Nippon A&L 307R) were mixed and uniformly dissolved in deionized water (at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (3).

[0066] Comparative Example 1 80.7 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (commercially available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.6 parts by weight of conductive carbon black (commercially available from Timcal under the trade name Super-P), and 6.7 parts by weight of poly(acrylic acid), PAA, were mixed and uniformly dissolved in deionized water (for at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (4).

[0067] Comparative Example 2 78.9 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (commercially available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.3 parts by weight of conductive carbon black (commercially available from Timcal under the trade number Super-P), 5 parts by weight of carboxymethyl cellulose (CMC) (commercially available from Daicel Chemical industries under the trade number CMC-2200), and 3.8 parts by weight of styrene butadiene rubber (SBR) (commercially available from Cino Group or S-insight technology under the trade number Nippon A&L 307R) were mixed and uniformly dissolved in deionized water (at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (5).

[0068] Comparative Example 3 78.9 parts by weight of SiO / C (a mixture of silicon oxide and carbon) (available from Kaijin New Energy Technology Co., Ltd. under the trade name KYX-2), 12.3 parts by weight of conductive carbon black (available from Timcal under the trade number Super-P), 0.5 parts by weight of chitosan (molecular weight about 300,000) (CAS: 9012-76-4, available from sigma-aldrich), 4.5 parts by weight of carboxymethylcellulose (CMC) (available from Daicel Chemical industries under the trade number CMC-2200), and 3.8 parts by weight of styrene butadiene rubber (SBR) (available from Cino Group or S-insight technology under the trade number Nippon A&L 307R) were mixed and uniformly dissolved in deionized water (at least 4 hours) (22.5 wt % solids and 77.5 wt % deionized water) to obtain a negative electrode active layer composition (6).

[0069] negative electrode Example 5 A copper foil (commercially available from Chang Chun Group under trade number BFR-F) (to become a negative electrode current collecting layer) was prepared. Then, the negative electrode active layer composition (1) was applied to the copper foil by blade coating to form a coating. Then, the coating was rolled using a rolling machine at a compression ratio of 25% to 30%. Then, after drying at 120° C., a negative electrode (1) having a negative electrode active layer (1) (thickness of about 50 μm) was obtained.

[0070] The resistivity of the negative electrode active layer (1) was measured using a four-probe resistance meter (DU-5211 Ohm Meter, Delta United), and the results are shown in Table 1.

[0071] The method for measuring the resistivity of the negative electrode active layer included the following steps: The sample was placed in a four-probe resistivity meter. The probe was brought into contact with the surface of the sample under a pressure of 0.08 MPa. After contact, the system was allowed to stand for 3 seconds before measuring the resistivity with the four-probe resistivity meter.

[0072] Comparative Example 4 Except for replacing the negative electrode active layer composition (1) with the negative electrode active layer composition (4), Comparative Example 4 was carried out in the same manner as the negative electrode preparation method disclosed in Example 5 to obtain a negative electrode (2) having a negative electrode active layer (2) (thickness: about 50 μm).

[0073] The resistivity of the negative electrode active layer (2) was measured using a four-probe resistance meter (DU-5211 Ohm Meter, Delta United), and the results are shown in Table 1.

[0074] [Table 1]

[0075] As shown in Table 1, the resistivity of the negative electrode active layer was not significantly changed by adding the polymer of the present disclosure to the negative electrode active layer composition.

[0076] Example 6 Except for replacing the negative electrode active layer composition (1) with the negative electrode active layer composition (2), Example 6 was carried out in the same manner as the negative electrode preparation method disclosed in Example 5 to obtain a negative electrode (3) having a negative electrode active layer (3) (thickness: about 50 μm).

[0077] The adhesion between the negative electrode active layer (3) and the negative electrode current collecting layer was measured, and the results are shown in Table 2.

[0078] According to GB2792-1998, the adhesive strength was measured by a 180° peel test using a tensile tester (DS2-20N, IMADA).

[0079] Example 7 Except for replacing the negative electrode active layer composition (1) with the negative electrode active layer composition (3), the negative electrode of Example 7 was prepared in the same manner as in Example 5 to obtain a negative electrode (4) having a negative electrode active layer (4) (thickness: about 50 μm).

[0080] The adhesion between the negative electrode active layer (4) and the negative electrode current collecting layer was measured, and the results are shown in Table 2.

[0081] Comparative Example 5 Except for replacing the negative electrode active layer composition (1) with the negative electrode active layer composition (5), Comparative Example 5 was performed in the same manner as the negative electrode preparation method disclosed in Example 5 to obtain a negative electrode (5) having a negative electrode active layer (5) (thickness: about 50 μm).

[0082] The adhesion between the negative electrode active layer (5) and the negative electrode current collecting layer was measured, and the results are shown in Table 2.

[0083] Comparative Example 6 Except for replacing the negative electrode active layer composition (1) with the negative electrode active layer composition (6), Comparative Example 6 was performed in the same manner as the negative electrode preparation method disclosed in Example 5 to obtain a negative electrode (6) having a negative electrode active layer (6) (thickness: about 50 μm).

[0084] The adhesion between the negative electrode active layer (6) and the negative electrode current collecting layer was measured, and the results are shown in Table 2.

[0085] [Table 2]

[0086] As shown in Table 2, compared to the negative electrode active layer (5) obtained in Comparative Example 5, the composition used to prepare the negative electrode active layer (3) in Example 6 further contains the polymer of the present disclosure (which can react with carboxymethyl cellulose (CMC) and active material), and therefore the adhesion between the negative electrode active layer and the negative electrode current collecting layer is improved. In addition, compared to the negative electrode active layer (6) obtained in Comparative Example 6, the adhesion between the negative electrode active layer and the negative electrode current collecting layer in Example 6 is further improved because the chitosan is replaced with chitosan having a lithium sulfonate group. Furthermore, compared to Example 6, the amount of polymer in the composition of Example 7 is increased, and therefore the adhesion between the negative electrode active layer and the negative electrode current collecting layer in Example 7 is further improved.

[0087] Negative electrode performance (half-cell evaluation)

[0088] Example 8 The negative electrode (1) of Example 5, a polypropylene (PP) separator (commercially available from Celgard under trade number 2320) (thickness about 20 μm), and metallic lithium (diameter 6 mm, thickness 1 mm) (to serve as a counter electrode) were prepared.

[0089] The negative electrode, separator and positive electrode were then arranged in sequence (the negative electrode active layer of the negative electrode facing the separator and the lithium foil of the positive electrode facing the separator) and sealed into a coin cell (CR2032) (size 3.2 mm (thickness) × 20 mm (width) × 20 mm (length), and then a liquid electrolyte (commercially available from S-insight technology) was injected into the coin cell to obtain a battery (1).

[0090] The charge and discharge capacities of the first cycle charge / discharge of battery (1) were then measured at constant current (0.1 C) and 25° C. using a potentiostat (commercially available from Biologic under the trade name VMP3) to determine the irreversibility ratio. The results are shown in Table 3. The capacity retention of battery (1) was then measured. The results are shown in Table 3. The capacity retention was measured by determining the discharge specific capacity of the first cycle charge / discharge and the discharge specific capacity of the 50th cycle charge / discharge at 25° C. and a charge and discharge rate of 0.2 C / 0.2 C.

[0091] Comparative Example 7 A battery (2) was obtained by carrying out Comparative Example 7 in the same manner as in Example 8, except that the negative electrode (1) was replaced with the negative electrode (2).

[0092] The charge and discharge capacities of the battery (2) in the first charge / discharge cycle were then measured at constant current (0.1C) and 25°C using a potentiostat (available from Biologic under the trade name VMP3) to determine the irreversible ratio. The results are shown in Table 3. The capacity retention of the battery (2) was then measured. The results are shown in Table 3.

[0093] [Table 3]

[0094] As shown in Table 3, when the polymer of the present disclosure is further added to the composition of the negative electrode active layer, the discharge capacity of the first charge / discharge cycle of the battery is improved and the cycle life of the battery is also extended.

[0095] Example 9 Example 9 was carried out in the same manner as in Example 8 to prepare the battery, except that the negative electrode (1) was replaced with the negative electrode (3), to obtain a battery (3).

[0096] The charge and discharge capacities of the battery (3) in the first charge / discharge cycle were then measured at constant current (0.1C) and 25°C using a potentiostat (available from Biologic under the trade name VMP3) to determine the irreversible ratio. The results are shown in Table 4. The capacity retention of the battery (3) was then measured. The results are shown in Table 4.

[0097] Example 10 Example 10 was carried out in the same manner as in Example 8 to prepare the battery, except that the negative electrode (1) was replaced with the negative electrode (4), to obtain a battery (4).

[0098] The charge and discharge capacities of the battery (4) in the first charge / discharge cycle were then measured at constant current (0.1C) and 25°C using a potentiostat (available from Biologic under the trade name VMP3) to determine the irreversibility ratio. The results are shown in Table 4. The capacity retention of the battery (4) was then measured. The results are shown in Table 4.

[0099] Comparative Example 8 Comparative Example 8 was carried out in the same manner as in Example 8 to prepare the battery, except that the negative electrode (1) was replaced with the negative electrode (5), to obtain a battery (5).

[0100] The charge and discharge capacities of the battery (5) in the first charge / discharge cycle were then measured at constant current (0.1C) and 25°C using a potentiostat (available from Biologic under the trade name VMP3) to determine the irreversibility ratio. The results are shown in Table 4. The capacity retention of the battery (5) was then measured. The results are shown in Table 4.

[0101] Comparative Example 9 A battery (6) was obtained by carrying out Comparative Example 9 in the same manner as in Example 8, except that the negative electrode (1) was replaced with the negative electrode (6).

[0102] The charge and discharge capacities of the battery (6) in the first charge / discharge cycle were then measured at constant current (0.1 C) and 25° C. using a potentiostat (available from Biologic under the trade name VMP3) to determine the irreversibility ratio. The results are shown in Table 4. The capacity retention of the battery (6) was then measured. The results are shown in Table 4.

[0103] [Table 4]

[0104] As shown in Table 4, compared with the battery (5) of Comparative Example 8, the composition used to prepare the negative electrode of Example 9 further contains the polymer of the present disclosure, so that the discharge capacity of the charge / discharge in the first cycle is improved, the irreversible ratio is reduced, and the cycle life of the battery is extended. In addition, the capacity retention rate of the battery (6) of Comparative Example 9 at the 50th charge / discharge cycle is almost 0%. Compared with Comparative Example 9, the negative electrode of Example 9 is prepared by replacing chitosan with chitosan having a lithium sulfonate group, so that the discharge capacity of the charge / discharge in the first cycle is improved, the irreversible ratio is reduced, and the cycle life of the battery is extended.

[0105] According to an embodiment of the present disclosure, the polymer of the present disclosure has a lithium sulfonate group, so that it can react with a compound having a hydroxyl group or a silicon-containing compound.By adding the polymer of the present disclosure, the composition of the present disclosure can form a structure with lithium replenishment functionality and high mechanical strength, which improves the efficiency and cycle life of the battery.

[0106] It will be apparent that various modifications and variations can be made to the methods and materials disclosed. It is intended that the specification and examples be considered as exemplary only, with the true scope of the disclosure being indicated by the following claims and their equivalents. [Explanation of symbols]

[0107] 10...Negative electrode 12...Negative electrode active layer 14...Negative electrode current collecting layer 20…Separator 30...Positive electrode 32...Cathode active layer 34...Positive electrode current collecting layer 40...Electrolyte 100...battery

Claims

1. 1. A composition comprising: A component (A) containing a polymer (A-1) having any one of the following repeating units and carboxymethyl cellulose (A-2), Component (B) which is a binder; Component (C) which is a negative electrode active material; wherein the weight ratio of component (A) to component (B) is from 1:1 to 1:

9. 【Chemistry 1】 (In the formula, R 1 is hydrogen or an acetyl group.)

2. 2. The composition according to claim 1, wherein the weight ratio of the polymer (A-1) to the carboxymethyl cellulose (A-2) is from 99:1 to 1:

19.

3. 2. The composition of claim 1, wherein the ratio of the total weight of components (A) and (B) to the weight of component (C) is from 1:5 to 1:

15.

4. The composition of claim 1 further comprising component (D), which is an electrically conductive material.

5. 5. The composition of claim 4, wherein the ratio of the total weight of components (A) and (B) to the weight of component (D) is from 1:1 to 1:

9.

6. A negative electrode comprising a negative electrode active layer made from the composition of claim 1.

7. A battery, The negative electrode according to claim 6 , A separator; A positive electrode and wherein the negative electrode is separated from the positive electrode by the separator.

Citation Information

Patent Citations

  • Electrode for lithium nonaqueous electrolyte battery, positive electrode collector for lithium nonaqueous electrolyte battery, and its manufacturing method

    JP2009277660A

  • Lithium secondary battery and binder for anode of the lithium secondary battery

    US20190173086A1

  • Process for preparing a sulfonated chitosan

    US5229504A

  • Non-aqueous electrolyte power storage element and power storage device

    WO2020184125A1